In Vitro Root Formation in Dendrobium Orchid Plantlets with IBA - Aktar, S; Nasiruddin, KM; Huq, H (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The study was conducted at the USDA Biotechnology Laboratory, Department of Biotechnology, Bangladesh Agricultural University, Mymensingh during May to June 2006 to investigate the effect of different concentrations of IBA (0, 0.5, 1.0, 1.5 and 2.0 mg/l) with Vacin and Went (VW) medium and charcoal on root formation in Dendrobium orchid. Four parameters such as number of roots plantlet-1, length of root, fresh weight of root and days required for root formation were recorded at three DAIs (10, 20 and 30). The use of different concentrations of IBA had significant effects on the parameters examined. The best results were obtained from 1.0 mg/l IBA treatment in which the number of root was 1.81 plantlet-1, length of root 0.35 cm, fresh weight of root 0.16g at 30 DAI and the minimum days to root formation was 10.8. Key words: In vitro root formation, Dendrobium orchid, IBA. DOI = 10.3329/jard.v5i1.1457 J Agric Rural Dev 5(1&2), 48-51, June 2007